Application of DNA barcodes in identification of ginseng samples in the genus Panax L. - Hương, Lê Thanh; Linh, Nguyễn Nhật; Minh, Bùi Mạnh; Hạnh, Hà Hồng; Huệ, Huỳnh Thị Thu; Hải, Nông Văn; Huân, Hà Văn; Hiền, Lê Thị Thu (Vietnam Journal of Biotechnology, 2018)
Identification of species based on DNA sequences (DNA barcodes) is an aid to a taxonomic classification using morphological characteristics. DNA barcoding uses standard short genomic regions that are universally present in target lineages and has sufficient sequence variation to identify species in the genus. A variety of loci has been suggested as DNA barcodes for plants, including genes and non-coding regions in the nuclear and plastid genomes such as psbA-trnH, matK, rbcL, and ITS. In this study, we evaluated five potential DNA barcodes including 18S, ITS, matK, psbA-trnH, and rbcL for their ability to distinguish between species across our samples in the genus Panax L. Multiple alignments with 41 GenBank sequences selected from 9 species showed that the 18S region had the highest level of average similarity (99.87 %), followed by rbcL, matK, psbA-trnH, and ITS regions with lower levels of average similarities (99.27 %, 98.66 %, 96.82 % and 96.50 %, respectively). The phylogenetic trees showed that four of eleven ginseng samples were Panax vietnamensis Ha et Grushv., and three samples were Panax stipuleanatus with bootstrap values of 100 %. However, sequences of all five screened loci in the last four samples, which were considered as Panax bipinnatifidus based on morphological characteristics, were highly similar to Panax stipuleanatus with the level of sequence similarity reached 99.81 % - 100 %. In addition, our results showed that of five investigated DNA regions, ITS, and psbA-trnH were the most promising barcodes that could identify P. vietnamensis Ha et Grushv. and P. stipuleanatus species within the genus Panax L.